KEPEMIMPINAN TRUMP DAN NASIONALISME SUMBER DAYA: REFLEKSI TERHADAP KEMANDIRIAN DOKTRIN PERTAHANAN INDONESIA - Afrilian Sukarno Timur; Rahmad Saerodin, Tarsisius Susilo, Tedy Basuki, Ignatius Widi Nugroho (INTELIGENSIA MEDIA, 2026)
This study examines Donald Trump’s leadership characterized by resource nationalism under the “America First” policy and its implications for Indonesia’s defense logistics self-reliance strategy and doctrine. Geopolitical polarization across multiple domains (energy, technology, cyber, information) during Trump’s era was marked by an emphasis on national self-reliance, for example, withdrawing from global agreements (Paris Accord) and pushing full exploitation of domestic energy resources. Trump’s leadership style has been described as populist, protectionist, isolationist, and nationalist, often pursuing transactional “deal-making” to advance U.S. interests. Prior studies discuss Trump’s policies broadly, but have yet to explore their impact on Indonesia’s defense independence concept. Using a descriptive- qualitative approach and comparative case study, this research juxtaposes the “America First” strategy (USA) with “Indonesia First” efforts in achieving self-reliance in the defense sector. Findings indicate Trump’s policies of defense re-industrialization and energy “dominance” in the U.S. provide valuable lessons for Indonesia to strengthen its defense equipment and logistics autonomy in line with Pancasila values and the spirit of berdikari (standing on one’s own feet). Indonesia should develop a self-reliant defense posture supported by a strong domestic industry and strategic resource reserves, while still engaging internationally under its independent-and-active foreign policy. Indonesia’s future defense doctrine should embody “Active Self-Reliance”: achieving autonomy in defense capabilities, yet remaining proactive in defense diplomacy. This approach would enhance the Indonesian Armed Forces’ readiness amid global disruptions and ensure the long-term sovereignty and dignity of Indonesia’s defense.